Pemanfaatan Starategi Bisnis Omnichannel Marketing pada UMKM Kabupaten OKU Timur - Lestari, Dwi; Fasa, Muhammad Iqbal; Suharto, Suharto (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2023)
The rapid development of technology causes consumer tastes to change. With advances in the field of digitalization, it encourages consumers to behave instantaneously. This opens opportunities for MSMEs in terms of expanding the marketing of their products. One of them is implementing an omnichannel marketing business strategy through the Instagram platform. This research aims to describe the use of omnichannel marketing by MSMEs in East OKU Regency using descriptive qualitative research methods. The results of the study show that omnichannel marketing can shape MSME branding so that it can increase E-WoM (electronic word of mouth) so that product sales by MSME players experience an increase. This research is expected to be able to provide input regarding the use of omnichannel marketing business strategies for MSMEs.